Strategic Analysis of the Billboard Tax Collection System. Efforts to Increase Local Tax Revenue Depok City - Andrayanti, Iin; Reza Aulia Wicaksono; Tri Waluyo Prehantio; Laila Amalia (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
One of the potential taxes in Depok City is billboard tax. Low public awareness is currently one of the obstacles to billboard tax collection in Depok City so that it becomes a challenge for tax officials related to increasing awareness of paying taxes, so how the collection system strategy must be formulated by the Depok City Government to change the mindset so that taxpayer awareness can increase so that it can contribute to creating optimal public services. This research focuses on the billboard tax collection system strategy in an effort to increase local taxes in Depok City and the method used is a qualitative method. Based on the results of the analysis, organisational and institutional strategies have been running well, but strategic programs need to be improved in the socialisation of billboard tax. Resource support strategies need additional training for employees, and internal and external supervision and administration must be tightened to improve compliance and legal effectiveness, billboard tax realisation in the last 4 years, from 2019 to 2022, has continued to increase, but has decreased in 2023, so there needs to be some special strategies to increase revenue realisation at the Depok City Regional Finance Agency. Keywords: Strategy, Billboard Tax, Local Tax Revenue